Система автономного керування траєкторією безпілотного літального апарата - Гула, Володимир Андрійович; Hula, Volodymyr Andriiovych (Національний університет "Львівська політехніка", 2024)
Гула В.А., Ділай І.В. (керівник). Система автономного керування траєкторією безпілотного літального апарата. Магістерська кваліфікаційна робота. – Національний університет «Львівська політехніка», Львів, 2025. Розширена анотація Безпілотні літальні апарати (БПЛА) сьогодні стали невід’ємною складовою сучасних технологій, що застосовуються у військовій, цивільній та промисловій сферах. Залежно від призначення, конструкції та способу управління, БПЛА поділяються на низку категорій, серед яких важливе місце займають FPV-дрони (First Person View). Ці дрони вирізняються тим, що оператор здійснює керування, спостерігаючи політ у реальному часі через камеру, встановлену на борту апарата. Однак широке застосування FPV-дронів у бойових умовах супроводжується серйозними викликами. Зокрема, в умовах активного застосування засобів радіоелектронної боротьби (РЕБ) виникає серйозна загроза для ефективного управління дроном — приглушення каналів управління та передачі відеосигналу призводить до повної втрати контролю над дроном. Це знижує ефективність бойового застосування FPV-дронів і ставить під загрозу виконання поставлених завдань. Метою роботи є розроблення системи автономного керування траєкторією безпілотного літального апарата, що дасть можливість автоматизувати процес керування польотом, усунути людський фактор, підвищити стійкість до впливу РЕБ та загальну ефективність дронів у військових операціях. Для досягнення мети було поставлено такі завдання: 1. Провести аналіз проблеми автономного керування траєкторією БПЛА. 2. Розробити концепцію системи автономного керування FPV-дроном. 3. Обґрунтувати вибір технічних засобів системи. 4. Розробити алгоритми автономного керування FPV-дроном. 5. Реалізувати апаратну та програмну частину системи У першому розділі магістерської роботи виконано аналіз об'єкта дослідження — FPV-дрона як різновиду безпілотного літального апарата, особливо вразливого до впливу засобів радіоелектронної боротьби. Розглянуто класифікацію БПЛА [1], конструкцію та принципи функціонування FPV-дронів [2]. Обґрунтовано необхідність автономного керування як критично важливого елементу для підвищення ефективності дронів у бойових умовах. Виконано огляд наукових досліджень і технологій у цій сфері, що створює теоретичне підґрунтя для розробки власної системи. У другому розділісформовано концепцію системи автономного керування FPV-дроном із візуальним відстеженням цілі. Запропонована дворівнева архітектура: контролер польоту (нижній рівень) та мікрокомп’ютер з обробкою відео (верхній рівень). На основі огляду сучасних прошивок [3] обґрунтовано вибір Betaflight. Аналіз протоколів взаємодії [4-6] та результати експериментів підтвердили доцільність використання CRSF замість MAVLink. Для візуального відстеження, згідно з дослідженням алгоритмів [7], обрано CSRT-трекер з бібліотеки OpenCV, як одного з найбільш точних алгоритмів, здатного стабільно працювати навіть у складних умовах зйомки. У третьому розділіобґрунтовано вибір апаратних компонентів для створення FPV-дрона. Комплектація підібрана на основі практичних рекомендацій волонтерських спільнот такий як Social Drone та Victory Drones. Обрано мікрокомп’ютер Raspberry Pi Zero 2 W із камерою для реалізації логіки та візуального відстеження. В основі дрона — 10-дюймова рама Mark4 V2 з контролером Speedybee F405 V4 і моторами ReadyToSky 3115 900KV. Для стабільного зв’язку використовується ELRS-приймач із підтримкою CRSF. Відеосигнал передається за допомогою передавача RushFPV Max Solo 2.5W з круговою антеною. Пропелери HQProp 10x5x3 забезпечують ефективну тягу. Усі компоненти підібрані з урахуванням сумісності, продуктивності та перевіреної на практиці надійності. У четвертому розділі на основі [8] розроблено власні алгоритми відстеження цілі та автономного керування FPV-дроном. Алгоритм відстеження дає можливість в реальному часі визначати положення об’єкта на відеопотоці, а керуючий алгоритм — формувати сигнали на основі координатної похибки. Обидва алгоритми інтегровані в єдину систему, що забезпечує автономну реакцію дрона на зміну положення цілі в кадрі без втручання оператора. У п’ятому розділі, на основі інструкції [9], зібрано та налаштовано апаратну частину FPV-дрона. Виконано прошивку ESC, налаштування польотного контролера через Betaflight, калібрування сенсорів і приймача. Також налаштовано Raspberry Pi Zero 2 W: встановлено ОС, активовано інтерфейси та забезпечено зв’язок із контролером. У шостому розділіреалізовано програмну частину системи автономного керування FPV-дроном. Створено програму для виявлення цілі, обчислення координатної похибки та формування керуючих сигналів через протокол CRSF.Для взаємодії з протоколом CRSF були створені допоміжні функції на основі напрацювань [10]. Програму адаптовано для Raspberry Pi із автоматичним запуском. Локальне тестування у Betaflight підтвердило коректність роботи.

Hula V.A., Dilay I.V. (head). Autonomous Trajectory Control System for an Unmanned Aerial Vehicle. Master's Qualification Thesis – Lviv Polytechnic National University, Lviv, 2025. Abstract Unmanned aerial vehicles (UAVs) have become an integral part of modern technologies used in military, civil, and industrial sectors. Depending on their purpose, design, and control methods, UAVs are categorized into several types, with FPV drones (First Person View) holding a significant position. These drones are distinctive in that the pilot operates them while observing the flight in real-time through a camera installed on the drone. However, the widespread use of FPV drones in combat conditions poses serious challenges. In particular, under active radio-electronic warfare (EW) conditions, the effective control of the drone is at serious risk — interference with control channels and video signal transmission can result in a complete loss of control over the drone. This reduces the efficiency of FPV drones in combat operations and endangers the accomplishment of assigned tasks. The goal of this work is to develop a system for autonomous trajectory control for UAVs, which will automate the flight process, eliminate human factors, enhance resistance to EW interference, and improve the overall effectiveness of drones in military scenarios. To achieve this goal, the following tasks were set: 1. Conduct an analysis of the issue of autonomous trajectory control for UAVs. 2. Develop a concept for an autonomous control system for FPV drones. 3. Justify the choice of technical components for the system. 4. Develop algorithms for autonomous control of FPV drones. 5. Implement the hardware and software components of the system. In the first section of the master’s thesis, an analysis of the research object — the FPV drone as a type of UAV, particularly vulnerable to EW interference — is conducted. The classification of UAVs [1], as well as the design and operating principles of FPV drones [2], are reviewed. The necessity for autonomous control, as a critical component for increasing FPV drones' efficiency in combat scenarios, is substantiated. A review of scientific research and technologies in this field provides the theoretical basis for developing the proposed system. In the second section, the concept of an autonomous FPV drone control system with visual target tracking is established. A two-level architecture is proposed: the flight controller (lower level) and the microcomputer with video processing capabilities (upper level). Based on a review of contemporary firmware [3], Betaflight is selected as the optimal solution. The analysis of communication protocols [4–6] and experimental results confirmed the feasibility of using CRSF instead of MAVLink. For visual tracking, according to the analysis of algorithms [7], the CSRT tracker from the OpenCV library is chosen as one of the most precise algorithms capable of operating reliably even under challenging shooting conditions. In the third section, the choice of hardware components for building an FPV drone is substantiated. The configuration is selected based on practical recommendations from volunteer communities such as Social Drone and Victory Drones. A Raspberry Pi Zero 2 W microcomputer with a camera is used for implementing logic and visual tracking. The foundation of the drone is a 10-inch Mark4 V2 frame with a Speedybee F405 V4 controller and ReadyToSky 3115 900KV motors. An ELRS receiver supporting CRSF ensures stable connection, while video signal transmission is facilitated by a RushFPV Max Solo 2.5W transmitter with a circular antenna. HQProp 10x5x3 propellers provide effective thrust. All components are selected for compatibility, performance, and proven reliability based on practical implementation. In the fourth section, based on the findings in [8], custom algorithms are developed for target tracking and autonomous control of the FPV drone. The tracking algorithm enables real-time detection of an object’s position in the video stream, while the control algorithm generates signals based on coordinate error. Both algorithms are integrated into a unified system that provides autonomous drone reactions to changes in the target’s position within the frame without operator intervention. In the fifth section, based on the instructions provided in [9], the hardware components of the FPV drone are assembled and configured. ESC firmware is updated, the flight controller is configured using Betaflight, and sensors and the receiver are calibrated. Furthermore, the Raspberry Pi Zero 2 W is set up by installing an Operating System, activating interfaces, and establishing communication with the controller. In the sixth section, the software system for autonomous FPV drone control is implemented. A program is developed for target detection, calculation of coordinate errors, and generation of control signals using the CRSF protocol. Auxiliary functions for CRSF protocol interaction are created, based on [10]. The program is adapted for Raspberry Pi, with automatic startup functionality. Local testing in Betaflight has confirmed the software’s correctness.
Autonomous Trajectory Control System for an Unmanned Aerial Vehicle
Keywords: 3.174.00.00